The Kurawa's Redemption: Contemporary Punakawan Navigate the Kurawa’s Shifting Allegiances for Gatotkaca Heroism and Subversion of Traditional Morality in Satria Dewa's Gatotkaca Film - Iswara, Aufa Auly Nona Bunga Evelyn Bias (Baca Dulu Publisher, 2025)
The Gatotkaca character from comics has been adapted into several cultural products, one of which is a film. This study examines the reimagining of traditional Javanese morality in Satria Dewa: Gatotkaca through the lens of the Kurawa's potential redemption. This article analyzes the reinterpretation of the transformation of the Gatotkaca character who represents Javanese idealism into a modern superhero who symbolizes criticism of Kurawa superpower in a global context. Focusing on how contemporary Punakawan navigate the Kurawa’s shifting allegiances, this research explores the film's subversion of traditional morality as presented in the original Mahabharata. Through an analysis of narrative structure, character archetypes, and symbolic representation, the study investigates the ways in which the film portrays the Kurawa's capacity for good and the challenges this poses to established notions of heroism and villainy. It also considers how the contemporary Punakawan act as moral guides, mediators, and catalysts in the Kurawa's journey, influencing Gatotkaca's understanding of justice, compassion, and the complexities of human nature. Ultimately, this research aims to shed light on how Satria Dewa: Gatotkaca uses the narrative of redemption to reflect contemporary social values and ethical dilemmas, while simultaneously redefining the role of the Punakawan in shaping a more nuanced understanding of Javanese heroism.